Microplastics in the soil environment: Occurrence, risks, interactions and fate - A review - Xu, Baile; Liu, Fei; Cryder, Zachary; Huang, Dan; Lu, Zhijiang; He, Yan; Wang, Haizhen; Lu, Zhenmei; Brookes, Philip C.; Tang, Caixian; Gan, Jay; Xu, Jianming (Critical reviews in environmental science and technology, 2020)
The issue of microplastic pollution emerged from the marine environment, but the terrestrial environment is estimated to receive annually 4-23 times more plastic wastes. Microplastic pollution in the soil environment has thus begun to elicit great concern. This review summarizes the observed effects of microplastic pollution on soil ecosystems as well as sorption and transport behaviors of microplastics in such environments. Microplastic pollution has been detected in various soils including agricultural/farmland, greenhouse, home garden, coastal, industrial, and floodplain soils. Microplastics affect soil physical and chemical properties, microbial and enzyme activities, and plant growth, and also pose adverse ecotoxicological effects to soil fauna. These effects depend on the concentration, size, and shape of microplastics, as well as soil texture. Microplastics are known to sorb organic and inorganic pollutants, possibly affecting the distribution of these substances in soil. Existing evidence demonstrates the negligible effect of microplastics on bioaccumulation of contaminants in soil fauna. The horizontal and vertical transport of microplastics can be facilitated by soil fauna. Pollutants associated with microplastics may disperse further following the transport of microplastics in soil. This review also highlights perspectives for future research on microplastics in soil.